Penentuan Pembebanan Maksimum Transformator Daya Yang Menyuplai Personal Computer (PC) - Prasetijo, Hari; Susilawati, Hesti (Dinamika Rekayasa, 2009)
Personal computer is electronic equiment that use solid state device, such as rectifiers, so it to be source of harmonic current. Harmonic current is sinusoidal current with multiple frequency of fundamental current which will be increase power losses because increasing effective current and frequency. In electric distribution system, transformer is component with highest power losses. They are consit of DC losses (Pdc) that influence by effective current, eddy current (PEC) and other stray losses (POSL) which influence by effective current and their frequency. This study involved increasing transformer power losses with assume that transformer supply in full load condition to personal computer. Analyzes following IEEE Std. C57.110-1998 with comparing determination maximum transformer loading use current spectrum from spectrum analyzer equipment and conversion produce Mathlab from current wave time domain to current wave frequency domain. The result are maximum transformer loading is 97,84 use spectrum analyzer and 97,84 use Mathlab sofware.